(untitled) (Anclajes, 2022)
Valeria Luiselli began her writing project with the essay Papeles falsos (2010), after a series of failed attempts at writing fiction. However, a year later she published her first novel, Los ingrávidos (2011), which takes up many of the questions raised in her first book. Through a careful reading of some of the themes that Luiselli’s texts persistently examine, we analyze the author’s literary operations in each of these cases. We recognize a similar logic behind these operations: different forms of translation based on a process of constant displacement and which also construct a migrant aesthetic.